Methods of signal processing applied to speech and language for objective assessment of cognitive function in ageing and psychiatry - Rapčan, Viliam (Trinity College (Dublin, Ireland). Department of Electronic & Electrical Engineering, 2014)
Ageing is associated with a change in cognitive function. Impaired cognitive function is the biggest limiting factor to independence in older adults. Cognitive decline does not appear suddenly, but occurs gradually over varying periods of time.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin